Hexapeptide-11 is a novel modulator of the proteostasis network in human diploid fibroblasts - Aimilia D. Sklirou; Marianna Ralli; Maria Dominguez; Issidora Papassideri; Alexios-Leandros Skaltsounis; Ioannis P. Trougakos (Redox Biology, 2015)
Despite the fact that several natural products (e.g. crude extracts or purified compounds) have been found to activate cell antioxidant responses and/or delay cellular senescence the effect(s) of small peptides on cell viability and/or modulation of protective mechanisms (e.g. the proteostasis network) remain largely elusive. We have thus studied a hexapeptide (Hexapeptide-11) of structure Phe–Val–Ala–Pro–Phe–Pro (FVAPFP) originally isolated from yeast extracts and later synthesized by solid state synthesis to high purity. We show herein that Hexapeptide-11 exhibits no significant toxicity in normal human diploid lung or skin fibroblasts. Exposure of fibroblasts to Hexapeptide-11 promoted dose and time-dependent activation of proteasome, autophagy, chaperones and antioxidant responses related genes. Moreover, it promoted increased nuclear accumulation of Nrf2; higher expression levels of proteasomal protein subunits and increased proteasome peptidase activities. In line with these findings we noted that Hexapeptide-11 conferred significant protection in fibroblasts against oxidative-stress-mediated premature cellular senescence, while at in vivo skin deformation assays in human subjects it improved skin elasticity. Finally, Hexapeptide-11 was found to induce the activity of extracellular MMPs and it also suppressed cell migration. Our presented findings indicate that Hexapeptide-11 is a promising anti-ageing agent. Keywords: Hexapeptide-11, Human fibroblasts, Proteasome, Proteostasis, Senescence, Chaperone, Antioxidant responses